2018
DOI: 10.3390/ijms19123931
|View full text |Cite
|
Sign up to set email alerts
|

Class I Phosphoinositide 3-Kinase PIK3CA/p110α and PIK3CB/p110β Isoforms in Endometrial Cancer

Abstract: The phosphoinositide 3-kinase (PI3K) signalling pathway is highly dysregulated in cancer, leading to elevated PI3K signalling and altered cellular processes that contribute to tumour development. The pathway is normally orchestrated by class I PI3K enzymes and negatively regulated by the phosphatase and tensin homologue, PTEN. Endometrial carcinomas harbour frequent alterations in components of the pathway, including changes in gene copy number and mutations, in particular in the oncogene PIK3CA, the gene enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 115 publications
(180 reference statements)
0
21
0
Order By: Relevance
“…Class IA has p110 (α/β/δ, which are gene products of PIK3CA/PIK3CB/PIK3CD, respectively) as the catalytic subunit that interacts with p85 which acts as the regulatory subunit. 47,12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Class IA has p110 (α/β/δ, which are gene products of PIK3CA/PIK3CB/PIK3CD, respectively) as the catalytic subunit that interacts with p85 which acts as the regulatory subunit. 47,12…”
Section: Introductionmentioning
confidence: 99%
“…2,21 The most common mutations being H1047R of the kinase domain and E542K and E545K of the helical domain. 4,21 Kinase domain mutation does not require the involvement of the RBD with the membrane protein RAS but depends on p85α for activation. 11,39 H1047R mutation causes structural transformations in the kinase domain which increases the membrane association of PI3Kα, thereby increasing the lipid kinase activity.…”
Section: Introductionmentioning
confidence: 99%
“… 172 174 As for gynecological cancers, this pathway is overactivated in OC (~70%), 175 177 as well as EC and CC. 178 180 In EC, the mutation rates of PI3K and PTEN were high, especially in the POLE subgroup. 20 In vitro model of CC, mTOR inhibitors markedly reduced the expression level of HPV E7 protein, inducing apoptosis.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that miR-155 is one of the most crucial miRNAs in MS as it regulates MS risk genes PIK3R1 and PIK3CA and correlates with severity of the disease [49]. These genes encode p85-α and p110-α proteins, members of phosphoinositide 3-kinase (PI3K) family [66,67]. Abnormalities in PI3K contribute to, e.g., cancer development, neurological and immunological dysfunctions, dendritic cells functioning, EAE pathogenesis and demyelination in MS [49].…”
Section: Mir-155 and Immune Responsementioning
confidence: 99%